2011
DOI: 10.1021/bi200202y
|View full text |Cite
|
Sign up to set email alerts
|

Activated ERK2 Is a Monomer in Vitro with or without Divalent Cations and When Complexed to the Cytoplasmic Scaffold PEA-15

Abstract: The extracellular signal-regulated protein kinase, ERK2, fully activated by phosphorylation and without a His6-tag, shows little tendency to dimerize with or without either calcium or magnesium ions when analyzed by light scattering or analytical ultracentrifugation. Light scattering shows that ~ 90% of ERK2 is monomeric. Sedimentation equilibrium data (obtained at 4.8–11.2 μM ERK2) with or without magnesium (10 mM) are well described by an ideal one-component model with a fitted molar mass of 40,180 ± 240 Da … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 44 publications
(122 reference statements)
3
51
0
Order By: Relevance
“…But, in several reports, the His-tag did affect biophysical/biochemical properties and has the propensity to promote protein dimerization/oligomerization (Amor-Mahjoub et al, 2006;Wu and Filutowicz, 1999). It is interesting to note that removal of the His-tag from Ets-1, one of well-defined ERK2 substrate in the nucleus, decreases its binding affinity to ERK2 by 1.5-fold (Kaoud et al, 2011). The influence of His-tag on ERK2 dimerization was also found in other studies in relation with divalent cations.…”
Section: Reports On Dimeric or Monomeric Phosphorylated Erk2 In Vitrosupporting
confidence: 60%
See 4 more Smart Citations
“…But, in several reports, the His-tag did affect biophysical/biochemical properties and has the propensity to promote protein dimerization/oligomerization (Amor-Mahjoub et al, 2006;Wu and Filutowicz, 1999). It is interesting to note that removal of the His-tag from Ets-1, one of well-defined ERK2 substrate in the nucleus, decreases its binding affinity to ERK2 by 1.5-fold (Kaoud et al, 2011). The influence of His-tag on ERK2 dimerization was also found in other studies in relation with divalent cations.…”
Section: Reports On Dimeric or Monomeric Phosphorylated Erk2 In Vitrosupporting
confidence: 60%
“…Although the authors also suggested the existence of a dimeric association of ERK2, its quantity was vanishingly small and negligible. A more thorough biophysical investigation on the monomer-dimer equilibrium of activated ERK2 was recently carried out by employing various experimental tools including light scattering, analytical ultracentrifuge and nuclear magnetic resonance spectroscopy (Kaoud et al, 2011). All the experimental results in this study indicated that tagless active ERK2 was a monomer and there was no propensity of homodimeric association.…”
Section: Reports On Dimeric or Monomeric Phosphorylated Erk2 In Vitromentioning
confidence: 80%
See 3 more Smart Citations